Enzyme-Responsive Materials as Carriers for Improving Photodynamic Therapy - Liu, Houhe; Yang, Fanwen; Chen, Wenjie; Gong, Teng; Zhou, Yi; Dai, Xiaoyan; Leung, Wingnang; Xu, Chuanshan (Frontiers in Chemistry, 2021)
Photodynamic therapy (PDT) is a mini-invasive therapy on malignancies via reactive oxygen species (ROS) induced by photosenitizer (PS) upon light irradiation. However, poor target of PS to tumor limits the clinical application of PDT. Compared with normal tissues, tumor tissues have a unique enzymatic environment. The unique enzymatic environment in tumor tissues has been widely used as a target for developing smart materials to improve the targetability of drugs to tumor. Enzyme-responsive materials (ERM) as a smart material can respond to the enzymes in tumor tissues to specifically deliver drugs. In PDT, ERM was designed to react with the enzymes highly expressed in tumor tissues to deliver PS in the target site to prevent therapeutic effects and avoid its side-effects. In the present paper, we will review the application of ERM in PDT and discuss the challenges of ERM as carriers to deliver PS for further boosting the development of PDT in the management of malignancies.